Pengaruh Persepsi Risiko, Kemudahan Penggunaan Dan Kepercayaan Terhadap Kepuasan Serta Dampaknya Pada Niat Beli Ulang (Studi Pada Pengguna Aplikasi Shopee Di Kota Semarang) - Zeni Rahmawati; Endang Tjahjaningsih (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine the influence of risk perception (X1), ease of use (X2), and trust (X3) on satisfaction (Y1) and its impact on repurchase intention (Y2) of Shopee application users in the city of Semarang. The research method used is a quantitative method.The data source uses a questionnaire via Google Form for 100 respondents with purposive sampling methodology. Hypothesis testing uses multiple linear regression using statistical-based data processing, namely SPSS. The population in this study are Shopee application users in the city of Semarang. The research results show that risk perception has a positive and significant effect on satisfaction, ease of use has a positive and significant effect on satisfaction, trust has no effect on satisfaction and satisfaction has a positive and significant effect on repurchase intention. Keywords: Risk Perception, Ease of Use, Trust, Satisfaction, Repurchase Intention